Stochastic Analysis of an Adaptive Line Enhancer/Canceler With a Cyclostationary Input - Bershad, Neil J.; Eweda, Eweda; Bermudez, Jose C. M. (IEEE transactions on signal processing, 2016)
This paper studies the second moment behavior of the adaptive line enhancer (ALE)/adaptive line canceler (ALC) for a cyclostationary input consisting of a fixed amplitude random phase sine wave plus a white Gaussian process with periodic power variations. Both transient and steady-state results are shown to be in good-to-excellent agreement with Monte Carlo simulations. The main conclusion is that periodic input power variations cause periodic processing gain variations of the ALE/ALC with the same period as the input power. However, these variations do not cause a large degradation in the ALE/ALC performance.